THE LGORITHMIC BASICS OF MEASUREMENTS - A. A. Moskvitin; A. B. Cheboksary; A. V. Duplishchev (Современная наука и инновации)
The paper describes a technique that allows you to outline the scope of possible (in principle) measuring devices and classify them according to scales corresponding to their measurement procedures. And also the algorithm is described and the corresponding software is created that im-plements the specified algorithm of the general method of searching for universal scales of the cor-responding rank for each measuring device. The research is based on the principle of phenomenological symmetry of Yu.I. Kulakov and concerns only a certain subclass of universal theories. For this purpose, the following definition of the empirical structure is introduced. The triple (M,N,p) - empirical structure, if appropriate (giv-en by (n + m)-local relation Rm,n,p satisfies the condition (Vii... in gM) (Vai... am g N) Rm,n,p (ii, in; ai, am); in this case, the pair of numbers r = (n, m) is called the rank of this structure, and if М п N= 0, then the number k = n + m is called its complexity. It is assumed that М п N= 0. All considerations relate to the empirical structure of rank. Solutions of the functional equa-tion f(u,v,w) = f(f(u,v,t), f(s,v,t), f(s,v,w)) are sought in the class of locally linear functions decom-posable in the Taylor series at each point. The basis for solving this problem is to find the function of re-grading the scale of the device to the canonical form. To do this, the corresponding overgrading hypothesis is formulated and tested. The implementation of the set of re-grading functions is based on the approximation method using or-thogonal Chebyshev polynomials for the case of equidistant points. The measurement tool selection algorithm uses an inductive user interface to make applica-tion programs simpler by breaking down functionality into screens or pages that are easier to both describe and understand. This allows you to both expand the range of users and reduce the amount of their thoughts that do not relate to the essence of the problem being solved (i.e., simplify the pro-cess of solving the problem on a computer), while maintaining its scientific value.